Management of maxillary alveolar bone fracture and severely intruded maxillary central incisor: report of a case. Issue 5 (11th January 2012) - Yonezawa, Hisanobu; Yanamoto, Souichi; Hoshino, Tomonori; Yamada, Shin‐Ichi; Fujiwara, Taku; Umeda, Masahiro
<x xml:space="preserve">Abstract</x> Abstract – An 11‐year‐old male who injured his maxilla and right maxillary central incisor and lip during a fall was presented to our hospital. His lower lip and upper gingiva were lacerated with swelling and epistaxis, and he had a maxillary alveolar bone fracture and severe intrusion of the right maxillary central incisor, which had penetrated the floor of the nasal cavity with avulsion. Under local anesthesia, we repositioned the incisor and bone segment and fixed them with a titanium micromesh plate and self‐tapping screws and splints. The incisor was also treated by root canal 3 days after the operation and was restored with a crown. We performed root canal filling 1 month later. Five months later, the plate and screws were removed. In prognosis of our case, no symptoms of inflammatory root resorption or ankylosis have observed for more than 1 year and 6 months of follow up based on both clinical and radiographic findings.